Femtosecond photoelectron diffraction on laser-aligned molecules: Towards time-resolved imaging of molecular structure - Boll, R.; Anielski, D.; Bostedt, C.; Bozek, J. D.; Christensen, L.; Coffee, R.; De, S.; Decleva, P.; Epp, S. W.; Erk, B.; Foucar, L.; Krasniqi, F.; et al. (My University, 2013)
We demonstrate an experimental method to record snapshot diffraction images of polyatomic gas-phase molecules, which can, in a next step, be used to probe time-dependent changes in the molecular geometry during photochemical reactions with femtosecond temporal and angstrom spatial resolution. Adiabatically laser-aligned 1-ethynyl-4-fluorobenzene (C8H5F) molecules were imaged by diffraction of photoelectrons with kinetic energies between 31 and 62 eV, created from core ionization of the fluorine (1s) level by ≈80 fs x-ray free-electron-laser pulses. Comparison of the experimental photoelectron angular distributions with density functional theory calculations allows relating the diffraction images to the molecular structure.